Success rates and outcomes of laparoscopic mesh sacrohysteropexy. (16th December 2019) - Daniels, Samuel; Robson, Danielle; Palacz, Magdalena; Howell, Stuart; Nguyen, Tran; Behnia‐Willison, Fariba
Abstract : Background: Uterovaginal prolapse is a prevalent gynaecological issue, which can have a negative impact on the quality of life of women. Hysterectomy and vaginal repair are conventional treatments to address apical prolapse; however, women are increasingly requesting uterine‐preserving alternatives. Aims: This study aimed to evaluate the impact of laparoscopic mesh sacrohysteropexy on symptomatic prolapse from an Australian experience. Materials and Methods: This retrospective cohort study presents outcomes of 157 patients who underwent laparoscopic mesh sacrohysteropexy at a private practice in South Australia during 2007–2017. Primary outcome is the success rate according to the pelvic organ prolapse quantification (POP‐Q) system. Secondary measures included complication rates and patients identified as having Stages III‐IV prolapse and their outcomes. Results: The median age was 58 years (27–86 years), median parity was 2 (0–6), and median body mass index was 26.8 (23–29.9). One hundred and thirty‐four women had a laparoscopic hysteropexy and concurrent vaginal prolapse repair and four women had an isolated laparoscopic hysteropexy. The mean pre‐operative point C was 0.60. The mean change from pre‐operative point C to post‐operative point C was 7.6 cm ( P < 0.01). Of the 136 patients (98.6%) seen at post‐operative 4–6 weeks, all had Stage 0 POP‐Q scores. Prolapse recurrence was observed in 22 patients, while 116 patients remained cured at their last follow‐up. Prolapse recurrence was associated with anterior vaginal mesh, previous prolapse surgery, pre‐operative Stage III‐IV disease and number of vaginal deliveries. Conclusions: Laparoscopic mesh sacrohysteropexy is an effective and safe procedure with a high success rate comparable to available international data.